2017
DOI: 10.1194/jlr.m077313
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein C-III (Gln38Lys) variant associated with human hypertriglyceridemia is a gain-of-function mutation

Abstract: Recent cell culture and animal studies have suggested that expression of human apo C-III in the liver has a profound impact on the triacylglycerol (TAG)-rich VLDL production under lipid-rich conditions. The apoC-III Gln38Lys variant was identified in subjects of Mexican origin with moderate hypertriglyceridemia. We postulated that Gln38Lys (C3), being a gain-of-function mutation, promotes hepatic VLDL assembly/secretion. To test this hypothesis, we expressed C3 in McA-RH7777 cells and -null mice to contrast it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…In two families with severe FH, we discovered a heterozygous whole-gene duplication of PCSK9 with extremely high circulating PCSK9 levels [43]. As well, a gain-of-function mutation in APOC3 was revealed as a new cause for hypertriglyceridemia [68]. Our findings have also been individually impactful for our patients.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In two families with severe FH, we discovered a heterozygous whole-gene duplication of PCSK9 with extremely high circulating PCSK9 levels [43]. As well, a gain-of-function mutation in APOC3 was revealed as a new cause for hypertriglyceridemia [68]. Our findings have also been individually impactful for our patients.…”
Section: Discussionsupporting
confidence: 54%
“…We report our clinical and research experience with LipidSeq, a targeted hybrid panel designed for clinical resequencing of genomic loci known to be associated with dyslipidemia and related metabolic traits and disorders. Since 2014, the results from this panel have contributed to 39 publications reporting original scientific findings, including seven on FH [32,43,44,[46][47][48][49], seven on hypertriglyceridemia [42,45,[50][51][52][53][54], four on extremes of HDL cholesterol [39,[55][56][57], and 21 case reports [40,41,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. We have published an additional 15 reviews and methods articles related to this work [4, 5, 7, 11-13, 20, 34, 77-83].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was observed in vitro, as demonstrated by increased LPL inhibition by Q38K compared to WT protein, and in vivo. Consistent with previous reports, the selective expression of Q38K APOC3 in the liver of apoc3 KO mice was associated with hypertriglyceridemia 23 and we showed that this phenotype was associated with impaired postprandial TG clearance. These effects are consistent with our hypothesis that Q38K and A23T exert opposite effects on LPL-mediated hydrolysis of TG.…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesized that conversely, a putative GOF variant in apoC-III could display increased binding to TRL and exert increased inhibition of LPL activity. To test our hypothesis, we decided to investigate the biochemical properties of Q38K, a naturally-occurring variant of apoC-III that has been associated with increased TG levels 22,23 . We first investigated the inhibitory effects of WT, A23T and Q38K on LPL activity using a well-established in vitro assay 43 .…”
Section: The Naturally Occurring Q38k Variant Of Apoc-iii Has Increasmentioning
confidence: 99%
See 1 more Smart Citation